Gene network analyses point to the importance of human tissue kallikreins in melanoma progression - Landman Gilles; Rezze Gisele G; Almeida Otávio M; Esteves Gustavo H; Martins Waleska K; Marques Sarah M; Carvalho Alex F; L Reis Luiz F; Duprat João P; Stolf Beatriz S (BMC, 2011)
Abstract Background A wide variety of high-throughput microarray platforms have been used to identify molecular targets associated with biological and clinical tumor phenotypes by comparing samples representing distinct pathological states. Methods The gene expression profiles of human cutaneous melanomas were determined by cDNA microarray analysis. Next, a robust analysis to determine functional classifications and make predictions based on data-oriented hypotheses was performed. Relevant networks that may be implicated in melanoma progression were also considered. Results In this study we aimed to analyze coordinated gene expression changes to find molecular pathways involved in melanoma progression. To achieve this goal, ontologically-linked modules with coordinated expression changes in melanoma samples were identified. With this approach, we detected several gene networks related to different modules that were induced or repressed during melanoma progression. Among them we observed high coordinated expression levels of genes involved in a) cell communication (KRT4, VWF and COMP); b) epidermal development (KLK7, LAMA3 and EVPL); and c) functionally related to kallikreins (EVPL, KLK6, KLK7, KLK8, SERPINB13, SERPING1 and SLPI). Our data also indicated that hKLK7 protein expression was significantly associated with good prognosis and survival. Conclusions Our findings, derived from a different type of analysis of microarray data, highlight the importance of analyzing coordinated gene expression to find molecular pathways involved in melanoma progression.